Hazard Chart for Identification of Potential Landslide Due To the Presence of Residual Soil in the Himalayas - Ray A.; Kumar R.E.S.C.; Bharati A.K.; Rai R.; Singh T.N. (My University, 2025)
Shallow landslides involving residual soils are frequent all over the Himalayan Region. The study presents a general scheme for probabilistic landslide hazard analysis by giving a general overview of the effect of residual soil on slope stability and proposes a landslide hazard chart. The results obtained from the probabilistic analysis reveal that failure of the slope is not governed by any one parameter; rather, it depends on the critical combination of many physical parameters of the slope. The hazard chart will be used for initial identification of instability, thus indicating the priorities for landslide hazard management. © 2019, Indian Geotechnical Society.